Linguistic Defamiliarization in The Text of Ahmad Tohari’s Novel Trilogy - Asrofah, Asrofah; Rustono, Rustono; Supriyanto, Teguh; Mulyani, Mimi (Universitas Negeri Semarang, 2017)
This research is entitled Linguistic Defamiliarization in the text of Ahmad Tohari’s Trilogy. One of problems discussed is the form of linguistic defamiliarization in the text of Ahmad Tohari’s novels united in a trilogy. The purpose of this study is to describe the form of linguistic defamiliarization in the text. Theoretically, this research contributes (1) to adding a new insight about the writing Ahmad Tohari’s rhetorical style and (2) to the preparation or writing of the history of Indonesian literary theory. Meanwhile, among the practical benefits that can be obtained is the appreciation of interesting language and literature learning. This research is a qualitative descriptive study employing an analytical approach and hermeneutic technique. It was carried out in such a way because it was difficult to avoid using an eclectic method to analyze a novel. The use of integrated the methods was expected to get maximum results. The data in this study were linguistic data in the form of sentence fragments contained in the text of the novels in the trilogy, namely Ronggeng Dukuh Paruk, Lintang Kemukus Dini Hari, and Jentera Bianglala. The data were in the form of chunks of the characters’ speech and the author’s narration in the form of words, phrases, clauses, sentences and discourse that allegedly contained forms of defamiliarization. The data collection technique employed in this study was the documentary technique and first level of semiotic reading technique. The data collection technique used in this study can be described as follows, (1) reading the text of the trilogy employing the first level of semiotic reading technique, i.e. the heuristic reading. This reading technique was based on a linguistic convention; (2) keeping records of data coded according to the characteristics on the data cards; (3) classifying the data according to the types of problems, namely the forms defamiliarization at word, phrase, clause, sentence, and discourse levels. On the data analysis stage, a second level of reading technique was applied, that is the hermeneutic technique, to provide the overall meanings of the text. The results of this study show that the form of text defamiliarization in Ahmad Tohari’s trilogy are in all linguistic levels, i.e. word, phrase, clause, sentence and discourse ones. At the word level, the defamiliarization is in the form of connotative meaning utilization, exploiting the Javanese words, the use of foreign terms, the use of expletives, and the utilization of compositum. Meanwhile, at the phrase level it shows the use of endocentric attributive phrases, endocentric connective phrases, verbal phrases, noun phrases, and prepositional phrases. An the clause level it shows the use of verbal clauses, adjectival clauses, and nominal clauses. The sentences found in the text are in the form of simple sentences and compound/complex sentences with varied structural patterns, both compound and complex sentences.